Alterações antrópicas na dinâmica hidrossedimentar da bacia hidrográfica do Córrego Guaribas a partir da presença de canal artificial - Silva, Lara Luíza (2021)
The artificial channels are configured as open ditches in the terrain that aim at the transposition of water from one elevation of the terrain to another, the appropriation of spaces from these channels generates changes in the landscape dynamics, especially in the hydrogeomorphological processes between slopes and valley bottoms. This study therefore sought to understand the hydrosedimentological dynamics of artificial channels inserted in the Hydrographic Basin of the Córrego Guaribas located in the city of Uberlândia - MG through analysis of the variation of the flow, total dissolved solids (STD) and production of suspended sediments, the fields followed the 12-month interval (August 2019 to July 2020) to accompany local seasonal and landscape variations, allowing to understand how the presence of the artificial channel impacts and impacts the environment, as well as understanding its own dynamics. The results pointed to two artificial channels due to the new supply of water that is inserted in the channels through a bus made in the path, the dynamics of the channel was totally deferred until its entrance in the path. The analyzes were carried out on different fronts, primarily the artificial channel as unique including the monthly scenarios, in which it was observed that the artificial channel has its own dynamics not only dependent on external processes (precipitation, wind, flow speed etc.) but also having a strong communication with anthropic actions. After an analysis of the 10 sampling points (one point in the natural channel and nine in the artificial ones), each point presented a singular behavior and reaffirmed the idea of ​​the anthropic impacts acting in the channels (linked to the uses, mainly watering), the greatest variations present were the result of these actions. At the end, through the joint analysis of the sampling points, the existence of two artificial channels was justified from a certain point, thus comparative assessments were made between the three channels, artificial channel 1, artificial channel 2 and natural channel, where higher values ​​were observed flow and STD in the natural channel and sediment (g / L) in the artificial channels. It is concluded that the presence of artificial channels affect not only the hydrosedimentological dynamics but also has repercussions in the other landscape components, being important its consideration in the studies since its knowledge can contribute in the environmental planning and in the identification of its impacts, thus helping in the best watershed management.